O trabalho nos Centros de Atenção Psicossocial Álcool e outras Drogas (CAPS – AD) nos municípios de Santo André e Diadema (SP): desafios para a atuação profissional - Silva, Silvia Moreira da (2019)
This thesis aims at discussing the work of social workers, psychologists, and, peer workers in the services of Psychosocial Attention Network (RAPS), more specifically, within the Psychosocial Care Center for Alcohol and Other Drugs (CAPS-AD) of Diadema’s and Santo André’s cities. For that, it analyses in what ways the work precariousness, in the advance of neoliberal ideal scenario, has been impacting the praxis of these professionals, and it also presents the difficulties and the challenges facing the political and mental health contexto changes. To reach the mentioned objectives, a bibliographic review was made on the topics: labor, alienation, neoliberalism, psychiatrist reform, social services among others. In the field, to collect data, semi-structured interviews were conducted with seven professionals in the CAPS-AD and of Consultório na Rua – Street Clinic – of the targeted cities. As a result from the research, it was observed that the changes in the national mental health policy and the work precariousness affect the everyday work of these professionals and the multidisciplinary team on the RAPS services, causing them sickness, which also impacts on their work. With the policy change, a setback to an insane asylum model is possible to occur, which is a violator of mental health users’ human rights, in spite of the advances of the psychiatrist and sanitary reform, with the implementation of the Unique Health System (SUS) and of RAPS. The debate around the changes of the mental health policy needs to reach society and mainly users and families who are the target of these policies, aiming at guaranteeing the right to care and attention within RAPS in the communitarian, participative, democratic and autonomous logic, instead of the institutionalization of asylum services